2006
DOI: 10.1002/chem.200600377
|View full text |Cite
|
Sign up to set email alerts
|

Methylazacalixpyridines: Remarkable Bridging Nitrogen‐Tuned Conformations and Cavities with Unique Recognition Properties

Abstract: Methylazacalix[n]pyridines (n = 4, 8) and methylazacalix[m]arene[n]pyridines (m = n = 2, 4) have been synthesized by a convenient fragment coupling approach starting from 2,6-dibromopyridine, 2,6-diaminopyridine, and benzene-1,3-diamine. Thanks to the intrinsic electronic nature of nitrogen, which can adopt mainly sp(2) hybridization, allowing it variously to conjugate, partially conjugate, or not conjugate with the adjacent one or two pyridine rings, the resulting nitrogen-bridged calixpyridine derivatives ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(58 citation statements)
references
References 92 publications
4
54
0
Order By: Relevance
“…Literature data on the reactivity of 2,6dibromopyridine with 2,6-diaminopyridine (Scheme S1 †) confirm this view. 41,42 The available procedures for the synthesis of H 2 tpda indeed follow path (a) by reacting 2,6diaminopyridine with overstoichiometric 2-halopyridine (Hal = Cl, Br) and an added base (tBuOK or NaH) in refluxing benzene or THF. 40,[43][44][45][46] Although 2-chloropyridine gives better results, yields never exceed 60% even using a large excess of arylant.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Literature data on the reactivity of 2,6dibromopyridine with 2,6-diaminopyridine (Scheme S1 †) confirm this view. 41,42 The available procedures for the synthesis of H 2 tpda indeed follow path (a) by reacting 2,6diaminopyridine with overstoichiometric 2-halopyridine (Hal = Cl, Br) and an added base (tBuOK or NaH) in refluxing benzene or THF. 40,[43][44][45][46] Although 2-chloropyridine gives better results, yields never exceed 60% even using a large excess of arylant.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…By varying the reaction conditions, between one and all four of the pyrrole rings could be converted to chloropyridines. 127 Both benzene and pyridine rings could be utilised to build the macrocycle, with both cyclic tetramers and octamers being isolated ( Figure 5.54a-d) along with linear species. This means that isomeric mixtures are often obtained (we have only shown one isomer for each compound).…”
Section: Calixindoles Calixpyridines and Calixthiophenesmentioning
confidence: 99%
“…The introduction of hetero atoms, especially nitrogen atoms, on the bridges results in the formation of different conformations and cavities, owning to the fact that bridging nitrogen atoms can adopt sp 2 or sp 3 or both electronic configurations and can form various degrees of conjugations with the adjacent aromatic rings [38][39][40][41][42][43]48] . More importantly, when they interact with guest, the heteroatom-bridged calix(hetero)aromatic compounds can self regulate their conformations to best fit the guest, which enables their good recognition to both neutral molecules, such as diols, fullerenes, and metal cations [39][40][41]48] . We have demonstrated that methyazacalix [4] pyridine (MACP-4) (Figure 1), an outstanding example of heteroatom-bridged calix(hetero) aromatic compounds, was a powerful and selective ligand to metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroatom-bridged calix(hetero)aromatic compounds are an emerging generation of macrocyclic host molecules [35][36][37][38][39][40][41][42][43][44][45][46][47][48] . The introduction of hetero atoms, especially nitrogen atoms, on the bridges results in the formation of different conformations and cavities, owning to the fact that bridging nitrogen atoms can adopt sp 2 or sp 3 or both electronic configurations and can form various degrees of conjugations with the adjacent aromatic rings [38][39][40][41][42][43]48] .…”
Section: Introductionmentioning
confidence: 99%